On one class of modules over integer group rings of locally solvable groups - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study a Z G-module A in the case where the group G is locally solvable and satisfies the condition min–naz and its cocentralizer in A is not an Artinian Z-module. We prove that the group G is solvable under the conditions indicated above. The structure of the group G is studied in detail in the case where this group is not a Chernikov group.